2010
DOI: 10.1063/1.3536391
|View full text |Cite
|
Sign up to set email alerts
|

Contact Binaries: The Current State

Abstract: Lucy's model of contact binaries has been serving well since its development in 1968 as an excellent conceptual framework for internal structure and evolution studies of the W UMa type stars. Its over-constrained structural demands were recognized early, but -from the observational point of view -it was particularly appealing in its ability to explain W UMa-type binary light curves. Large numbers of photometric light curves of W UMa type binaries have been solved for geometrical parameters utilizing the clarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although the errors of the phenomenological parameters are not very large (up to few percent), there may be systematic errors up to a dozen percent due to the simplicity of the model. These estimates may be used as preliminary values for further modeling using extended physical models based on the Wilson & Devinney (1971) code and it's extensions (Wilson 1979(Wilson , 1994(Wilson , 2012(Wilson , 2014Zola et al 1997Zola et al , 2010Bradstreet 2005;Kallrath et al, 2009;Linnel 2012;Reed 2012;Rucinski 2010;Prsa et al 2012). Such study of eclipsing binaries with the CBNU observations are reported by Jeong & Kim (2013); Kim & Jeong(2012); Jeong & Kim (2011) and Kim et al (2010a).…”
Section: Discussionmentioning
confidence: 78%
“…Although the errors of the phenomenological parameters are not very large (up to few percent), there may be systematic errors up to a dozen percent due to the simplicity of the model. These estimates may be used as preliminary values for further modeling using extended physical models based on the Wilson & Devinney (1971) code and it's extensions (Wilson 1979(Wilson , 1994(Wilson , 2012(Wilson , 2014Zola et al 1997Zola et al , 2010Bradstreet 2005;Kallrath et al, 2009;Linnel 2012;Reed 2012;Rucinski 2010;Prsa et al 2012). Such study of eclipsing binaries with the CBNU observations are reported by Jeong & Kim (2013); Kim & Jeong(2012); Jeong & Kim (2011) and Kim et al (2010a).…”
Section: Discussionmentioning
confidence: 78%
“…Portegies Zwart & Leigh (2019) further argued that the production of compact twin BS binaries (with mass ratios close to unity) could in fact be the dominant channel or evolutionary pathway. We note briefly here a possible connection to contact binaries, called W UMa systems, many of which are know to host BSs (Rucinski 2010). The approximate distribution of predicted orbital periods for this mechanism are shown via the dashed black histograms in Figure 7.…”
Section: Triples With Inner Binaries Containing Ms Stars And/or Wdsmentioning
confidence: 98%
“…In some cases, the transfer proceeds steadily for a long time; in others mass and energy are exchanged in a common envelope; while in the most dynamic and interesting cases the interaction leads to a merger giving birth to a single star of unusual properties that cannot be produced by the evolution of a single star. We know that all of these processes do occur in nature yielding observable outcomes such as contact binaries (Smith 1984;Rucinski 2010), helium white dwarfs (WD) (Kippenhahn et al 1967(Kippenhahn et al , 1968, R Coronae Borealis stars (Clayton 2012), Type Iax supernovae (Jha 2017;Solheim 2010), and dwarf novae (Warner 2003;Frank et al 2002). Some of the largest explosions in the universe, Type Ia supernovae, are caused by the Roche-Lobe-overflow induced merger of two WD (Hillebrandt & Niemeyer 2000).…”
Section: Introductionmentioning
confidence: 99%